Optimalisasi Peralatan Tambang Komatsu HD 785 dan Caterpillar 6030 BH Menggunakan Metode Quality Control Circle Untuk Memenuhi Target Produksi Batu Gamping Pada PT. Semen Padang (Persero) Tbk. - M. Fadly; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract.The process of loading and hauling limestone at PT. Semen Padang from the mining front to the crusher uses a combination of Caterpillar 6030 BH Excavator and Komatshu 785 Dump Truck mining equipment. Limestone production target in August 2018 is 853,984 tons.This study uses the QCC method to increase the productivity of mining equipment. In the actual achievement before the increase in productivity of the digging equipment was 80,4 % and transport equipment 72,1 % of the production target in August 2018. Based on the Paretto analysis the main problem and the dominant cause of not optimal productivity of mining equipment was the amount of work time wasted 84, 5 hours / month for loading and unloading equipment and 102.88 hours / month for conveyance from available work time.By improving the wasted work time with the QCC method productivity increases to around 22,2 % for loading and hauling equipment 28 % of actual productivity. After increasing the time wasted to 27.97 hours / month for loading and unloading equipment and 28.7 hours / month of conveyance.Keywords: Excavator, Dump Truck, Produktivity, Quality Control Circle, Paretto